PENGEMBANGAN COMIC BOOK BERBASIS AUGMENTED REALITY MATERI KERAGAMAN BUDAYA INDONESIA SISWA KELAS IV UPT SDN SENTUL 4 KOTA BLITAR - Wahyu Difa Agustiya; Nur Amalia, Shofi; Wafa, Khoirul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to create a product developed from the 4th grade elementary school learning environment in the form of augmented reality-based comic book. In this research, ADDIE is used in a series of processes including analysis, design, development, implementation and evaluation (research and development) of models and development methods. The measurement tools used by researchers in this research are tests and questionnaires. Product validation tests are carried out by material, media and language experts, and surveys are evaluated by class teachers. Expert validation testing shows over 87% effectiveness. The eligibility test will be carried out 100% by the class teacher. Meanwhile, the calculated average category growth rate increased by 93.6%.